The determinants of preference for healthcare facilities in Calapan City, Oriental Mindoro - Santos, Vicente Jeronimo L.
Hospital administrators need to be aware of the healthcare needs of the clients and their preferences. This requires quality healthcare information to provide, preserve and expand healthcare services. Thus, this paper explored the Calapeños health economy to identify its influential determinants of preferences in choosing healthcare facilities.